Studi Potensi Interaksi Obat pada Pasien Diabetes Melitus Tipe-2 di Rumah Sakit Islam Jakarta Cempaka Putih - Katrin Olivia Panjaitan; Widya Handayani; Dini Permata Sari; Norman Dyanto (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to determine the demographic characteristics, description of potential drug interactions, and the relationship between demographics and number of drugs with potential drug interactions in patients with Type-2 Diabetes Mellitus in the Outpatient Installation of Jakarta Islamic Hospital Cempaka Putih. This study is an analytical observational study with a retrospective cross-sectional design with a total sampling of 200 prescriptions from January-March 2025. The sampling technique used total sampling, so that all prescriptions that met the research criteria were included as samples. Identification of interactions was carried out theoretically using the medscape drug interaction checker and drugs.com interactions checker, then analyzed descriptively and Chi-Square test with a 95% confidence level (α = 0.05). The results showed that patients were predominantly aged 56-65 years (44.5%) and >65 years (32.5%) with a relatively balanced gender distribution. Potential drug interactions were found in 61.0% of prescriptions, with moderate interactions (84.2%), major (10.5%), and minor (5.3%) predominating in severity. The most common type of interaction was pharmacodynamic (54.4%). Statistical tests showed that age (p=0.542) and gender (p>0.05) were not significantly associated with potential drug interactions, while the number of medications in the prescription was significantly associated (p<0.05). Thus, the potential for drug interactions in patients with Type 2 Diabetes Mellitus is more influenced by the complexity and number of medications used than demographic factors.